Cyclostratigraphy and paleoclimate analysis of the Lingshui Formation in Changchang Sag, Qiongdongnan Basin, China - Haizhang Yang; Wu Tang; Enze Xu; Shangfeng Zhang; Yaning Wang; Min Xu (Energy Geoscience, 2024)
The Qiongdongnan Basin, located in the sea between Hainan Island and the Xisha Islands, is a faulted Cenozoic basin on the northern continental margin of the South China Sea. The Changchang Sag, situated in the eastern part of the central depressional zone in the deepwater area of the Qiongdongnan Basin, exhibits a near EW-striking morphology and represents an important potential target for oil/gas exploration. However, the age of the interface of the Lingshui Formation remains controversial, which hinders a comprehensive understanding of the tectonic evolution and hydrocarbon accumulation pattern in the Changchang Sag. This study focuses on well A, located in the depositional center of the Changchang Sag, and employs cyclostratigraphic analysis to identify cyclic signals of the Milankovitch cycles recorded in the sedimentary strata. Spectral analysis of natural gamma logging data from this well reveals the presence of 405 kyr long eccentricity cycles, 100 kyr short eccentricity cycles, 39.3 kyr obliquity cycles, and 20.58 kyr age precession cycles. By employing astronomical tuning, a “floating” astronomical time scale of the Lingshui Formation spanning 5.483 million years (Myr) is established. The top interface of the Oligocene in the International Geological Time Scale 2020 (GTS2020), with a geological age of 23.03 Ma, is used as the time anchor to establish a high-precision absolute astronomical age framework for the Lingshui Formation. The results indicate that the bottom interface of the first member of the Lingshui Formation is dated at 23.79 Ma, the bottom interface of the second member is dated at 25.08 Ma, and the bottom interface of the third member is dated at 28.51 Ma. Additionally, the average sedimentation rate during this period is estimated to be 9.261 cm/kyr. Furthermore, paleoclimate and paleoenvironmental reconstructions were carried out through quantitative analysis of spore and pollen assemblages, as well as foraminifera within the Lingshui Formation. These analyses suggest that the deposition of the Lingshui Formation occurred under warm and humid temperate climatic conditions. The results of paleoclimate proxy analysis and comparative fitting analysis of the astronomical time scale confirm that the climate evolution during this period was influenced by astronomical orbital forces, such as eccentricity and precession.